Multidetector Computed Tomography (CT) in Evaluation of Congenital Cyanotic Heart Diseases - Enaba, Moanes M. (Pol J Radiol, 2017)
BACKGROUND: The aim of the study is to emphasize the role of 128 MSCT angiography in the diagnosis of congenital cyanotic heart diseases. MATERIAL/METHODS: This study included sixty patients and was conducted from December 2014 to July 2016 in the Multidetector CT unit of Zagazig University hospitals. All images included axial, MPR, MIP, and VRT and were interpreted in one session. Pulmonary veins were assessed for PAPVR or TAPVR, PDA, cardiac apex and heart chambers, interatrial or interventricular septal defects, pericardium, and site and size of the great veins (IVC and SVC). RESULTS: This study included 60 patients. Thirty-four were boys (56.7%), and 26 were girls (43.3%). The age ranged from nine months to five years, and the mean age was 34.5 months. We found the following anomalies: tetralogy of Fallot (15 patients, 25%), tricuspid atresia (12 patients, 20%), Ebstein’s anomaly (4 patients, 6.5%), pulmonic atresia or stenosis (7 patients, 11.5%), truncus arteriosus (6 patients, 10%), TGA (10 patients, 17%), and TAPVR (6 patients, 10%). CONCLUSIONS: MDCT proved to be an important modality for decision-making in patients with congenital cyanotic heart diseases.